Conceptualizing COVID‐19‐Related Career Concerns Using Bioecological Systems: Implications for Career Practice. Issue 4 (6th December 2021) - Belser, Christopher T.; Prescod, Diandra J.
Abstract : The COVID‐19 pandemic has affected many aspects of the global society, including the workforce, with many effects yet to be seen. Career professionals in various settings are positioned to support clients and students through pandemic‐related career concerns. Bronfenbrenner's (1979, 2001, 2005) bioecological systems model provides a framework that can aid in conceptualizing clients' and students' presenting issues within the complex nature of their environments. In this theoretical article, we contextualize COVID‐19‐related career concerns through a bioecological systems lens and integrate four contemporary approaches to career work. Two fictional case studies illustrate how career professionals can integrate these approaches.